(untitled) (Research, Society and Development, 2020)
The main objective of this work was to evaluate the basic sanitation conditions in three places of Pará State: Mosqueiro Island (Belém), Beira-Mar Community (Curuçá) and the neighborhood Centro de Vigia. A total of 90 questionnaires were applied, being divided into 24 questionnaires in the island of Mosqueiro, 32 in the Beira-Mar community and 34 in the neighborhood of Centro. The questionnaires were designed for semi-systematized interviews for the owners, with the purpose of obtaining information on the type of water supply, the general aspects of the destination of the family sewage and garbage. The studied sites varied in some basic sanitation requirements presenting good conditions in some parameters, however precariousness in others. In a way, these precariousness impacts the environment and the health of the population, due to the lack of infrastructure in the basic components and essential for the man who serves to provide better quality of life.